Freedom and Prosperity: The Impact of Political Rights and Civil Liberties on Economic Complexity - Irsan Hardi; Naftaly Mose; Stoyan Tanchev; Muhammad Ilhamsyah Siregar; Seyma Bozkaya (Heca Sentra Analitika, 2025)
As governance and economic sophistication become increasingly interconnected, understanding their relationship is crucial for shaping national growth strategies. This study investigates the impact of political rights and civil liberties on Indonesia’s economic complexity from 2006 to 2021 by disaggregating the Economic Complexity Index (ECI) into trade, technology, and research components. Indonesia serves as an ideal case study due to its dynamic political landscape, evolving civil liberties, and its strategic role as an emerging economy with untapped potential for economic diversification. While a growing body of literature explores the intersection of political and economic development in Indonesia, no prior study has specifically examined the relationship between the Freedom in the World ratings (as an indicator of political rights and civil liberties) and the distinct dimensions of ECI. The analysis employs Gaussian identity-link Generalized Linear Models (GLMs), with robustness checks using Robust Least Squares, and adopts a decomposition approach that includes a set of control variables such as GDP per capita and FDI inflow. The results across both the main and robustness check methods consistently show that political rights and civil liberties contribute positively to ECI-technology, but negatively affect ECI-trade and have no significant effect on ECI-research. These findings underscore the sector-specific nature of political and democratization influences on economic complexity in Indonesia and imply that they facilitate technological advancement but do not uniformly promote trade or research sophistication.